HTTP blocking in CN: facebook.com, instagram.com, medium.com, nytimes.com, reddit.com +5 more (China) - Voidly (2026)
CRITICAL severity censorship detected in China. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: CN-2026-0005
Keywords: censorship; CN; censorship; critical